Exclusive maternal breastfeeding, always ? - Urquizo Aréstegui, Raúl (2014)
Breastfeeding must be stimulated, supported and encouraged during antenatal control. Explanation on importance of breastfeeding for her and her child must be explained, preparing her and family mentally and physically for exclusive breastfeeding. In this article the importance of exclusive maternal breastfeeding is described, questions on delivery affecting breastfeeding are answered, and nutritional needs of the lactating woman are emphasized.